THE RESISTENCE OF KAWE LOCAL COMMUNITY TO THE MANAGEMENT OF MARINE NATURAL RESERVE AREA IN RAJA AMPAT - George Mentansan; Phil I Ketut Ardhana; I Nyoman Suarka; I Nyoman Dhana (Universitas Sebelas Maret, 2017)
This article aims to reveal why and how the resistance of Kawe local people to the managment of marine nature reserve area (SAP) in Raja Ampat. This study uses qualitative method with ethnography approach. The results of the study shows that the reasons for the resistance to the power carried out in the management of natural marine reserves area (SAP) is due to feeling of the local people in which they do not receive any benefits from the marine conservation. The underlying reason is economic, educational, and the lack of local employment factors that led to the rejection or resistence. The resistance is mobilized by the local community of Kawe by way of rejection, and in the collaboration with the fishermen from outside of Raja Ampat enganging fishing and destructive activities in areas that have been prohibited by the applicable laws and regulations.